Modeling and simulation of an effectual triangular slotted UWB flexible antenna for breast cancer detection and healthcare monitoring - Aparna Singh; R. K. Dwivedi; Vinod Kumar Singh; Manish Sharma; Kanhaiya Sharma; Bulent Yilmaz (PLoS ONE, 2025)
With refinements in electromagnetics, diverse medical applications have evolved to detect diseases efficaciously. Breast cancer, a dominant cause of mortality among women worldwide, necessitates early diagnosis and screening for timely medical intervention. This research establishes the design, simulation, and analysis of an advanced triangular slotted circular flexible Ultra-wideband (UWB) antenna optimized for breast cancer detection and healthcare monitoring. The proposed antenna employs an extensive frequency range of 2.95 GHz to 24.2 GHz, accomplishing an impressive impedance bandwidth of 156%. It authenticates directional and omnidirectional radiation patterns with compact dimensions of 46.3 × 52.6 × 1.076 mm³. Key aspects divulge a resonance frequency at 14.35 GHz with a significant input reflection coefficient of −37.8 dB. The antenna achieves a peak gain of 3.16 dB at 5.8 GHz, with efficiencies of 59.56% and 66.88% at 5.8 GHz and 4.48 GHz, respectively. A meticulous case study involving SAR evaluation confirms the antenna’s safe exposure levels. For a flat human phantom, SAR values are 0.774 W/kg at 13.5 GHz and 0.712 W/kg at 14.35 GHz for 10 gm of tissue. For the breast phantom model, SAR values are 0.201 W/kg at 11.4 GHz and 0.152 W/kg at 14.35 GHz for 10 gm of tissue. Besides that, the antenna’s flexible design promises an excellent execution under several bending conditions, making it ideal for wearable applications. These findings establish the antenna as an efficient solution for breast cancer detection and healthcare monitoring, combining safety, flexibility, and the aptness to ameliorate early diagnosis while lowering mortality rates. Wearable antennas are pivotal for advanced healthcare applications. This section presents the literature and discusses the work related to flexible UWB antenna designed for breast cancer detection and healthcare monitoring, tackling challenges in early diagnosis and patient care.